2017
DOI: 10.1016/j.envpol.2016.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and health impact evaluation based on simultaneous measurement of indoor and ambient PM2.5 in Haidian, Beijing

Abstract: Because people spend most of their time indoors, the characterization of indoor air quality is important for exposure assessment. Unfortunately, indoor air data are scarce, leading to a major data gap in risk assessment. In this study, PM concentrations in both indoor and outdoor air were simultaneously measured using on-line particulate counters in 13 households in Haidian, Beijing for both heating and non-heating seasons. A bimodal distribution of PM concentrations suggests rapid transitions between polluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 32 publications
3
28
2
1
Order By: Relevance
“…Outdoor PM 2.5 concentration in heating season was much higher than in non-heating season in this study, a seasonal difference that has also been reported in several other studies conducted in Beijing [ 30 , 53 , 77 , 78 ], but not consistent with the study conducted in Beijing by Han [ 60 ] which may due to the short sampling periods and the frequent and rapid transition between severe pollution events and clean days. Indoor PM 2.5 were significantly lower than outdoor in both seasons from Table 2 , similar results showed in other studies [ 59 , 60 , 61 ], but indoor PM 2.5 concentration was not different between two seasons from Table 5 , which may mainly due to the low indoor and outdoor exchange in heating season and the contributions of indoor sources. The median concentration of indoor PM 2.5 was 57.64 μg/m 3 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Outdoor PM 2.5 concentration in heating season was much higher than in non-heating season in this study, a seasonal difference that has also been reported in several other studies conducted in Beijing [ 30 , 53 , 77 , 78 ], but not consistent with the study conducted in Beijing by Han [ 60 ] which may due to the short sampling periods and the frequent and rapid transition between severe pollution events and clean days. Indoor PM 2.5 were significantly lower than outdoor in both seasons from Table 2 , similar results showed in other studies [ 59 , 60 , 61 ], but indoor PM 2.5 concentration was not different between two seasons from Table 5 , which may mainly due to the low indoor and outdoor exchange in heating season and the contributions of indoor sources. The median concentration of indoor PM 2.5 was 57.64 μg/m 3 .…”
Section: Discussionsupporting
confidence: 87%
“…Outdoor PM 2.5 is an important source of residential indoor PM 2.5 [ 12 , 13 , 15 , 64 ], and it was significantly correlated with indoor PM 2.5 concentrations in both seasons from the results of Spearman correlation analysis, and similar results also can be found in other studies [ 20 , 59 , 60 , 61 , 62 , 63 ]. Multiple linear regression analysis in Table 7 showed that with the increase of outdoor concentration, indoor PM 2.5 concentration also increased in both seasons.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…When solid fuels are used for cooking and heating, emissions from these activities dominate the indoor PM 2.5 sources. However, in the case of S4, PM 2.5 in indoor air is largely contributed by penetration of pollutants from the ambient environment (30).…”
Section: Resultsmentioning
confidence: 99%